This can be solved by factoring.
First, set the expression equal to zero.
![3x^2+5x-2=0](https://tex.z-dn.net/?f=3x%5E2%2B5x-2%3D0)
Then, find two the factors of
![ac](https://tex.z-dn.net/?f=ac)
whose sum is
![b](https://tex.z-dn.net/?f=b)
.
![6, -1](https://tex.z-dn.net/?f=6%2C%20-1)
Split
![b](https://tex.z-dn.net/?f=b)
into these two factors.
![3x^2+6x-x-2=0](https://tex.z-dn.net/?f=3x%5E2%2B6x-x-2%3D0)
Next, factor by grouping.
![3x(x+2)-1(x+2) = (3x-1)(x+2) = 0](https://tex.z-dn.net/?f=3x%28x%2B2%29-1%28x%2B2%29%20%3D%20%283x-1%29%28x%2B2%29%20%3D%200)
By the Zero Product Property, set each factor equal to zero.
![3x-1 = 0 \\ x = 1/3](https://tex.z-dn.net/?f=3x-1%20%3D%200%20%5C%5C%20x%20%3D%201%2F3)
![x+2=0 \\ x = -2](https://tex.z-dn.net/?f=x%2B2%3D0%20%5C%5C%20x%20%3D%20-2)
These are the solutions. The Complex Conjugate Root Theorem and the Fundamental Theorem of Algebra both state that, in essence, real and imaginary solutions come in pairs of two and every polynomial of degree
![n](https://tex.z-dn.net/?f=n)
has exactly
![n](https://tex.z-dn.net/?f=n)
complex roots, but real roots are also complex roots. That sounds confusing, but this just means that you're done.
Your answers are -2 and 1/3. There are two real roots.
Answer:
a. Mean = 155.1 grams
b. Standard deviation = 0.37
c. Fractional uncertainty = 0.074
Step-by-step explanation:
a. Average weight
This is same as the mean weight;
Mathematically, that would be; sum of the weights/ the number of weights
= (155.1 + 154.8 + 155.5 + 155.3 + 154.6)/5 = 775.3/5 = 155.06 which is approximately 155.1
b. Standard deviation
Mathematically; we calculate that using the formula;
√{(x-mean)^2/(N-1)}
Please check attachment for for the complete breakdown of this
c. Fractional uncertainty
= Standard deviation/number of measurements = 0.37/5 = 0.074
Answer:
the answer is D
Step-by-step explanation:
I don't know how to explain it very well but the line starts at 2 then ends at 8
Answer:
Option (1)
Step-by-step explanation:
By the inscribed angle theorem inside a circle,
"Measure of an inscribed angle is half the measure of the intercepted arc"
[m(arc AB)] = m(∠ABC)
m(arc AB) = 2[m(∠ABC)]
x = 2(41°)
x = 82°
Option (1) is the correct option.
Its an indirect proof, so 3 steps :-
1) you start with the opposite of wat u need to prove
2) arrive at a contradiction
3) concludeReport · 29/6/2015261
since you wanto prove 'diagonals of a parallelogram bisect each other', you start wid the opposite of above statement, like below :- step1 : Since we want to prove 'diagonals of a parallelogram bisect each other', lets start by assuming the opposite, that the diagonals of parallelogram dont bisect each other.Report · 29/6/2015261
Since, we assumed that the diagonals dont bisect each other,
OC≠OA
OD≠OBReport · 29/6/2015261
Since, OC≠OA, △OAD is not congruent to △OCBReport · 29/6/2015261
∠AOD≅∠BOC as they are vertical angles,
∠OAD≅∠OCB they are alternate interior angles
AD≅BC, by definition of parallelogram
so, by AAS, △OAD is congruent to △OCBReport · 29/6/2015261
But, thats a contradiction as we have previously established that those triangles are congruentReport · 29/6/2015261
step3 :
since we arrived at a contradiction, our assumption is wrong. so, the opposite of our assumption must be correct. so diagonals of parallelogram bisect each other.